Evaluating the impact of chemotherapy-induced nausea and vomiting on daily functioning in patients receiving dexamethasone-sparing antiemetic regimens with NEPA (netupitant/palonosetron) in the cisplatin setting: results from a randomized phase 3 study - Luigi Celio; Diego Cortinovis; Alessio Aligi Cogoni; Luigi Cavanna; Olga Martelli; Simona Carnio; Elena Collovà; Federica Bertolini; Fausto Petrelli; Alessandra Cassano; Rita Chiari; Francesca Zanelli; et al. (BMC Cancer, 2022)
Abstract Background The non-inferiority of dexamethasone (DEX) on day 1, with or without low-dose DEX on days 2 and 3, combined with oral NEPA (netupitant/palonosetron), compared with the guideline-consistent use of DEX was demonstrated in cisplatin. Here, we complete the analysis by assessing the impact of emesis on daily lives of patients receiving DEX-sparing regimens using the Functional Living Index-Emesis (FLIE). Methods Chemotherapy-naïve patients undergoing cisplatin (≥70 mg/m2), were given NEPA and DEX (12 mg) on day 1 and randomized to receive either 1) no further DEX (DEX1), 2) oral DEX (4 mg daily) on days 2–3 (DEX3), or 3) DEX (4 mg twice daily) on days 2–4 (DEX4; control). Patients completed the FLIE questionnaire on day 6 of cycle 1. Endpoints included the FLIE nausea domain, vomiting domain, and overall combined domain scores, as well as the proportion of patients with no impact on daily life (NIDL; overall score > 108). This was a protocol-planned analysis. Results In the DEX1 group, no significant differences were observed in the FLIE nausea score (48.9 [±1.8; SE] vs. 53.7 [±1.5]), vomiting score (56.6 [±1.4] vs. 58.7 [±0.8]) and overall score (105.6 [±2.8] vs.112.4 [±1.9]) versus DEX4 control; similar results were observed in the DEX3 group for nausea score (49.6 [±1.7]), vomiting score (58.2 [±1]) and overall score (107.8 [±2.4]) versus control. There were no significant between-group differences in the proportion of patients reporting NIDL. Conclusion Reducing DEX, when administered with NEPA, does not seem to adversely impact the daily functioning in patients undergoing cisplatin. Trial registration ClinicalTrials.gov NCT04201769 . Registration date: 17/12/2019 - Retrospectively registered.